Bispecific antibody-mediated redirection of NKG2D-CAR natural killer cells facilitates dual targeting and enhances antitumor activity - Congcong Zhang; Anja Waldmann; Winfried S Wels; Jasmin Röder; Anne Scherer; Malena Bodden; Jordi Pfeifer Serrahima; Anita Bhatti; Nina Müller; Pranav Oberoi (Journal for ImmunoTherapy of Cancer)
Background Natural killer group 2D (NKG2D) is an activating receptor of natural killer (NK) cells and other lymphocytes that mediates lysis of malignant cells through recognition of stress-induced ligands such as MICA and MICB. Such ligands are broadly expressed by cancer cells of various origins and serve as targets for adoptive immunotherapy with effector cells endogenously expressing NKG2D or carrying an NKG2D-based chimeric antigen receptor (CAR). However, shedding or downregulation of NKG2D ligands (NKG2DL) can prevent NKG2D activation, resulting in escape of cancer cells from NKG2D-dependent immune surveillance.Methods To enable tumor-specific targeting of NKG2D-expressing effector cells independent of membrane-anchored NKG2DLs, we generated a homodimeric recombinant antibody which harbors an N-terminal single-chain fragment variable (scFv) antibody domain for binding to NKG2D, linked via a human IgG4 Fc region to a second C-terminal scFv antibody domain for recognition of the tumor-associated antigen ErbB2 (HER2). The ability of this molecule, termed NKAB-ErbB2, to redirect NKG2D-expressing effector cells to ErbB2-positive tumor cells of different origins was investigated using peripheral blood mononuclear cells, ex vivo expanded NK cells, and NK and T cells engineered with an NKG2D-based chimeric receptor.Results On its own, bispecific NKAB-ErbB2 increased lysis of ErbB2-positive breast carcinoma cells by peripheral blood-derived NK cells endogenously expressing NKG2D more effectively than an ErbB2-specific IgG1 mini-antibody able to induce antibody-dependent cell-mediated cytotoxicity via activation of CD16. Furthermore, NKAB-ErbB2 synergized with NK-92 cells or primary T cells engineered to express an NKG2D-CD3ζ chimeric antigen receptor (NKAR), leading to targeted cell killing and greatly enhanced antitumor activity, which remained unaffected by soluble MICA known as an inhibitor of NKG2D-mediated natural cytotoxicity. In an immunocompetent mouse glioblastoma model mimicking low or absent NKG2DL expression, the combination of NKAR-NK-92 cells and NKAB-ErbB2 effectively suppressed outgrowth of ErbB2-positive tumors, resulting in treatment-induced endogenous antitumor immunity and cures in the majority of animals.Conclusions Our results demonstrate that combining an NKAB antibody with effector cells expressing an activating NKAR receptor represents a powerful and versatile approach to simultaneously enhance tumor antigen-specific as well as NKG2D-CAR and natural NKG2D-mediated cytotoxicity, which may be particularly useful to target tumors with heterogeneous target antigen expression.